Challenging corruption in Asia : case studies and a framework for action - Bolongaita, Emil P.; Bhargava, Vinay Kumar, 1945- (Washington : World Bank, 2004)
This book outlines a six-step approach to developing effective anti-corruption strategies tailored specifically to a country's pattern of corruption and conditions of governance.
Includes bibliographical references and index.
oif 01/04/15
Loan
Keywords: Political corruption -- Asia -- Case studies; Business enterprises -- Corrupt practices -- Asia -- Case studies; Business enterprises -- Corrupt practices -- Asia; Political corruption -- Asia